High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

Horsehair worms (Nematomorpha) of the Prosecco Hills UNESCO World Heritage site, Italy - Andreas Schmidt-Rhaesa; Renzo Perissinotto (Zoologischer Anzeiger, 2025)

The big, the small and the weird: A phylogenomic analysis of extant Priapulida - Jan Raeker; Arianna Lord; María Herranz; Gonzalo Giribet; Katrine Worsaae; Andreas Schmidt-Rhaesa (Molecular Phylogenetics and Evolution, 2025)

David versus Goliath: An interspecific comparison between small-sized Halicryptus spinulosus and large-sized Halicryptus higginsi (Priapulida) - Jan Raeker; Katrine Worsaae; Andreas Schmidt-Rhaesa (Zoologischer Anzeiger, 2024)

New morphological structures of Priapulus caudatus, Lamarck 1816 (Priapulida) and analysis of homologous characters across macroscopic priapulids - Jan Raeker; Katrine Worsaae; Andreas Schmidt-Rhaesa (Zoologischer Anzeiger, 2024)

Taxonomy and phylogeny of Dalytyphloplanida Willems et al., 2006 (Platyhelminthes: Rhabdocoela), with the description of a new family, a new genus, and sixteen new species from Cuba and Panama - Yander L. Diez; Marlies Monnens; Arlien Wuyts; Luc Brendonck; Patrick Reygel; Andreas Schmidt-Rhaesa; Tom Artois (Organisms Diversity & Evolution, 2023)
Twenty-two marine species of Dalytyphloplanida from Cuba, Panama, and Lanzarote are presented, sixteen of which are new to science. Five known species are recorded from Cuba: Kytorhynchus microstylus , Ceratopera paragracilis , Trigonostomum armatum , T . franki , and T . vanmecheleni . Neokytorhynchus pacificus is recorded for the first time in the Atlantic (Lanzarote). For one species, a new genus is erected to be included in a new family. A new genus and thirteen new species from Cuba and three new species from Panama are described. The new species are mainly distinguished from their congeners by the specific morphology of the copulatory structures. The new taxa are discussed in the context of a new phylogenetic analysis of Dalytyphloplanida. This analysis includes sequences of 238 species, 14 of which were sequenced for the first time. The phylogenetic analysis and the detailed morphology suggest that K . microstylus may constitute a complex of cryptic species. The internal phylogenetic relationships of Trigonostomum and Promesostoma were separately analysed to include new sequence data of the mitochondrial cox1 gene. These genera are shown to consist of several diagnosable clades, concurring with the results of early morphological studies of these taxa. Morphological and molecular data support the notion that Trigonostomum sinensis is a junior synonym of T . vanmecheleni , and we therefore propose their synonymisation. A new family is erected, Schockaertiidae fam. n. , to include a monophyletic clade of neodalyellids with a pharynx rosulatus and a copulatory bulb devoid of hard structures ( Schockaertia aprostatica gen. n. sp. n. and Einarella argillophyla ). We propose a new classification into families of Thalassotyphloplanida, which envolves elevating the status of Adenorhynchinae to family level (Adenorhynchidae status novus ). All previously recognised thalassotyphloplanid families are recovered as monophyletic (Kytorhynchidae, Byrsophlebidae, Promesostomidae, and Trigonostomidae). No support was found for the previously described subfamilies, except Paramesostominae, and we, therefore, propose to suppress these taxa.

Comparative molecular and morphological species delineation of Halammohydra Remane, 1927 (Hydrozoa)—with the description of four new species - Lenke Tödter; Katrine Worsaae; Andreas Schmidt-Rhaesa (Organisms Diversity & Evolution, 2023)
Whereas most cnidarians are macrofaunal, a few microscopic lineages have evolved, and some of them inhabit marine sediments. The meiofaunal genus with the most species is Halammohydra , comprising nine nominal species. Species are described with high intraspecific variability in, e.g., the number of tentacles and statocysts and the shape and length of tentacles and body, complicating morphological identification to species level. Additionally, there is not much molecular data available. This study aims to revise already described species with morphological and molecular methods, as well as, to delineate potential new species answering questions about their geographical distribution. For this, specimens were sampled at 16 locations in the Northwest Atlantic and two localities in the East Atlantic, documented with light microscopy, and fixed individually for sequencing (16S, 18S, and CO1). Herewith, morphological characters were linked to a specific sequence, enabling the testing of character variation within one molecular phylogenetic group. Phylogenetic analyses were conducted (Bayesian Interference and Maximum Likelihood) in combination with species delimitation tests (ABGD, GMYC, and bPTP). Four already described species were identified in the data sets, and all of these were found at multiple localities. Four new species are described. Overall, the combined molecular and morphological data acquisition revealed multiple new species and a high degree of sympatry in Halammohydra . This, together with the confirmed excessive intraspecific variation in morphological traits, underlines the necessity of molecular sequencing for the taxonomy and species identification of Halammohydra .

Cryptic species complex or an incomplete speciation? Phylogeographic analysis reveals an intricate Pleistocene history of Priapulus caudatus Lamarck, 1816 - Glafira Kolbasova; Andreas Schmidt-Rhaesa; Vitaly Syomin; Danila Bredikhin; Taras Morozov; Tatiana Neretina (Zoologischer Anzeiger, 2023)

Morphology of larval and postlarval stages of Priapulopsis bicaudatus (Danielssen, 1869) (Priapulida) from the north atlantic ocean - Andreas Schmidt-Rhaesa; Jan Raeker (Zoologischer Anzeiger, 2023)

Sixth International Scalidophora Workshop - Martin V. Sørensen; Maikon Di Domenico; Andreas Schmidt-Rhaesa (Zoologischer Anzeiger, 2023)

Editorial - Andreas Schmidt-Rhaesa; Alexandra Kerbl (Zoomorphology, 2022)

Ultrastructural organization of Halammohydra vermiformis Swedmark & Teissier, 1957 (Cnidaria: Hydrozoa) - Lenke Tödter; Andreas Schmidt-Rhaesa (Zoomorphology, 2022)
Within meiofauna, cnidarians are represented by only a few species most of which are in the genus Halammohydra Remane, 1927. It represents highly modified medusae. Information about this group is limited, which complicates its placement in the Cnidarian tree and the relationship to another meiofaunal cnidarian, Otohydra Swedmark & Teissier, 1958. This needs to be clarified with molecular, but also with morphological methods. In this study, the internal organization of H. vermiformis Swedmark & Teissier, 1957 from Sylt and Helgoland (Germany) was examined using transmission electron microscopy (TEM). The ultrastructure of both sexes is documented in this study, i.e. the gastric tube including gonadal compartment, aboral cone, statocysts and tentacles. It is proposed that spermatozoa and oocytes are not released into the water through the gastrodermis, but by rupture of the epidermis, because of structural changes in the epidermis. In both, male and female, there is an indent in the gastric tube and a gap of the mesoglea at the same position. Additionally, we describe the complex structure of the aboral cone with the specialized adhesive organ as well as the accumulation of myofibrils and neurites in the orally directed part of the cone, which indicates high controllability and ability to move in this region.

Reinhard Rieger Award - Andreas Schmidt-Rhaesa (Zoomorphology, 2020)

Editorial - Andreas Schmidt-Rhaesa (Zoomorphology, 2018)

Redescription of Xenodasys riedli (Gastrotricha: Macrodasyida) based on SEM analysis, with first report of population density data - Juliane Schuster; Sarah Atherton; M. Antonio Todaro; Andreas Schmidt-Rhaesa; Rick Hochberg (Marine Biodiversity, 2018)

Immunohistochemical analysis of the anterior nervous system of the free-living nematode Plectus spp. (Nematoda, Plectidae) - Stephan Henne; Andy Sombke; Andreas Schmidt-Rhaesa (Zoomorphology, 2017)

Celebrating 90 years of Zoomorphology - Andreas Schmidt-Rhaesa (Zoomorphology, 2014)

A new team for Zoomorphology - Andreas Schmidt-Rhaesa (Zoomorphology, 2012)

Comparative neuroanatomy of Caudofoveata, Solenogastres, Polyplacophora, and Scaphopoda (Mollusca) and its phylogenetic implications - Simone Faller; Birgen Holger Rothe; Christiane Todt; Andreas Schmidt-Rhaesa; Rudi Loesel (Zoomorphology, 2012)

The nervous system of Neodasys chaetonotoideus (Gastrotricha: Neodasys) revealed by combining confocal laserscanning and transmission electron microscopy: evolutionary comparison of neuroanatomy within the Gastrotricha and basal Protostomia - Birgen H. Rothe; Andreas Schmidt-Rhaesa; Alexander Kieneke (Zoomorphology, 2011)

Morphology and deep metazoan phylogeny - Andreas Schmidt-Rhaesa (Zoomorphology, 2009)

Architecture of the nervous system in two Dactylopodola species (Gastrotricha, Macrodasyida) - Birgen H. Rothe; Andreas Schmidt-Rhaesa (Zoomorphology, 2009)

Muscular architecture of Milnesium tardigradum and Hypsibius sp. (Eutardigrada, Tardigrada) with some data on Ramazottius oberhaeuseri - Andreas Schmidt-Rhaesa; Juliane Kulessa (Zoomorphology, 2007)

Ultrastructural observations of the testicular epithelium and spermatozoa of Pseudochordodes bedriagae (Gordiida, Nematomorpha) - Cristina De Villalobos; Mario Restelli; Andreas Schmidt-Rhaesa; Fernanda Zanca (Cell and Tissue Research, 2005)

Morphogenesis of Paragordius varius (Nematomorpha) during the parasitic phase - Andreas Schmidt-Rhaesa (Zoomorphology, 2005)

Filling the Gondwana gaps: new species and new reports of Beatogordius Heinze, 1934 (Nematomorpha) from Australia and Madagascar - Andreas Schmidt-Rhaesa; Malcom S. Bryant (Systematic Parasitology, 2004)

The musculature of horsehair worm larvae (Gordius aquaticus, Paragordius varius, Nematomorpha): F-actin staining and reconstruction by cLSM and TEM - Monika C. M. Müller; Ralf Jochmann; Andreas Schmidt-Rhaesa (Zoomorphology, 2004)

Are the genera of Nematomorpha monophyletic taxa? - Andreas Schmidt‐Rhaesa (Zoologica Scripta, 2002)
Twenty‐two genera of horsehair worms (Nematomorpha) have been described to date, one (Nectonema) from the marine environment and the remaining ones (taxon Gordiida) from freshwater. The aim of this investigation was to test whether the genera represent monophyletic taxa or are likely to be paraphyletic assemblages. The recognition and delimitation of monophyletic taxa are prerequisites for further systematic analyses. From the 15 nematomorph genera containing more than one species, autapomorphies can be found for five genera (Chordodes, Nectonema, Beatogordius, Acutogordius, Noteochordodes). In three further genera (Paragordius, Parachordodes, Gordionus), the evaluation of characters as autapomorphies is likely, but relies on further investigations. For seven genera (‘Gordius’, ‘Paragordionus’, ‘Euchordodes’, ‘Neochordodes’, ‘Pseudochordodes’, ‘Spinochordodes’, ‘Digordius’), no autapomorphy could be found. Five genera (‘Digordius’, Lanochordodes, Progordius, Pantachordodes, Pseudogordius) are likely to be synonymous with other genera, and one genus ( Chordodiolus ) has been synonymized with Beatogordius recently. The importance of high quality documentation of characters in investigations of nematomorph species is stressed.

Variation of cuticular characters in the Nematomorpha: studies on Gordionus violaceus (Baird, 1853) and G. wolterstorffii (Camerano, 1888) from Britain and Ireland - Andreas Schmidt-Rhaesa (Systematic Parasitology, 2001)

The evolutionary relationships of rotifers and acanthocephalans - James R. Garey; Andreas Schmidt-Rhaesa; Thomas J. Near; Steven A. Nadler (Hydrobiologia, 1998)